Smart contracts como solución eficiente a los nuevos problemas del consumidor en el e-commerce - Monsante Moy, Isabella; Novoa Suárez, Ariana; Quintanilla Gutiérrez, Alejandra (Pontificia Universidad Católica del Perú, 2021)
The exponential growth of e-commerce in Peru has generated new problems in the effectiveness of consumer rights and the consequent consumer distrust in e-commerce transactions. Government authorities have repeatedly mentioned that a solution to these problems would be the regulation of electronic consumer’s relationships established at national level. This solution goes on the same page with the tendency of the European Union to regulate digital markets. However, is the legislative initiative an ideal solution to solve the new problems generated by e-commerce?.In this article, the authors find that regulation of e-commerce would not completely solve the new problems generated by it. They evidence the necessity of utilizing market solutions based on new technological mechanisms such as smart contracts. These tools, together with the incentive of the authorities that protect consumers’ rights, will be able to efficiently solve the new problems that are generated in this new decade.

El crecimiento exponencial del e-commerce en el Perú ha generado nuevos problemas en el cumplimiento de los derechos de los consumidores y la consecuente desconfianza del consumidor en las transacciones de comercio electrónico. Diversas autoridades han propuesto como solución que se regulen las transacciones de e-commerce realizadas en el ámbito nacional, en línea con la tendencia de la Unión Europea a regular los mercados digitales. Sin embargo, ¿es la iniciativa legisladora una solución idónea para resolver los nuevos problemas generados por el e-commerce?.En el presente artículo, las autoras analizan cómo una ley de e-commerce no resolvería por completo los nuevos problemas generados por este y plantean la necesidad de contar con soluciones desde el mercado, elaboradas a partir de nuevos mecanismos tecnológicos como los smart contracts. Estas herramientas, junto con el incentivo de las autoridades que protegen derechos de los consumidores, podrán resolver de forma eficiente los nuevos problemas que se generan en esta nueva década.
Smart contracts as an efficient solution to the consumer’s distrust of e-commerce
Keywords: Consumidores; E-commerce; Smart contracts; Análisis de impacto regulatorio; Cooperación internacional; https://purl.org/pe-repo/ocde/ford#5.05.01